Obesity, Second Stage Duration, and Labor Outcomes in Nulliparous Women - Frolova, Antonina I.; Raghuraman, Nandini; Stout, Molly J.; Tuuli, Methodius G.; Macones, George A.; Cahill, Alison G. (American Journal of Perinatology, 2019)
Objective This study aimed to estimate second stage duration and its effects on labor outcomes in obese versus nonobese nulliparous women.Study Design This was a secondary analysis of a cohort of nulliparous women who presented for labor at term and reached complete cervical dilation. Adjusted relative risks (aRR) were used to estimate the association between obesity and second stage characteristics, composite neonatal morbidity, and composite maternal morbidity. Effect modification of prolonged second stage on the association between obesity and morbidity was assessed by including an interaction term in the regression model.Results Compared with nonobese, obese women were more likely to have a prolonged second stage (aRR: 1.48, 95% CI: 1.18–1.85 for ≥3 hours; aRR: 1.65, 95% CI: 1.18–2.30 for ≥4 hours). Obesity was associated with a higher rate of second stage cesarean (aRR: 1.78, 95% CI: 1.34–2.34) and cesarean delivery for fetal distress (aRR: 2.67, 95% CI: 1.18–3.58). Obesity was also associated with increased rates of neonatal (aRR: 1.38, 95% CI: 1.05–1.80), but not maternal morbidity (aRR: 1.06, 95% CI: 0.90–1.25). Neonatal morbidity risk was not modified by prolonged second stage.Conclusion Obesity is associated with increased risk of neonatal morbidity, which is not modified by prolonged second stage of labor.
Keywords: labor; obesity; second stage; second stage cesarean; second stage duration